Rock fracturing mechanisms by blasting - Torbica, Slavko; Lapčević, Veljko (Podzemni radovi, 2018)
Optimizing blast fragmentation and reducing the damage from it are two important research subjects in this field. Detonation and explosive charge induces three sets of tension cracks in the monolith rock. Radial tension cracks are formed under the influence of the pressure wave whose cylindrical propagation induces tension. Along with the explanation of how radial cracks are formed, formulation is given as to how their length can be calculated using laboratory and drill and blast parameters. Cracks subparallel with the free surface (face) are related with amounts of absorbed and recoverable strain energies. The distance between subsequent cracks can be calculated using the results of simple load-unload laboratory tests. Third sets of tension cracks are formed as a result of excessive deformation of the beam or cantilever formed by radial cracks. Once the length of the cracks and the distance between them are known, it is possible to apply these results for estimation of fragment sizes and blasting pattern design.